The Passivation Behavior of Sputter-deposited W-Zr Alloys in NaCl and NaOH Solutions - Shrestha, Prakash; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
The passivation behavior of the sputter-deposited amorphous or/and nanocrystalline W-Zr alloys is studied in 0.5 M NaCl and 1 M NaOH solutions at 25°C, open to air using corrosion tests and electrochemical measurements. Zirconium metal acts synergistically with tungsten in enhancing the corrosion resistance of the sputter-deposited W-Zr alloys so as to show lower corrosion rates than those of alloy-constituting elements (that is, tungsten and zirconium) in 0.5 M NaCl solution. In particular, corrosion rates of the binary W-Zr alloys containing 23-76 at % zirconium are more than one order of magnitude lower than that of tungsten (that is, about 0.8-1.1 × 10-3 mm.y-1) and even lower than that of the sputterdeposited zirconium. On the other hand, the corrosion rates of the W-Zr alloys containing 54-76 at% zirconium are nearly two orders of magnitude lower than that of tungsten and even about one order of magnitude lower corrosion rate than that of sputter-deposited zirconium metal in alkaline 1 M NaOH solution. These results clearly revealed that the simultaneous additions of both tungsten and zirconium metals to the sputter-deposited amorphous or nanocrystalline W-Zr alloys are effective in enhancing the corrosion resistance of the alloys in both 0.5 M NaCl and alkaline 1 M NaOH solutions at 25°C, open to air. The corrosion-resistant of all the examined binary W-Zr alloys in 0.5 M NaCl solution is higher than in 1 M NaOH solution at 25°C. In general, the open circuit potentials of all the examined W-Zr alloys are shifted to more noble direction with increasing the alloy zirconium content in both 0.5 M NaCl and 1 M NaOH solutions. Keywords: Sputter-deposited W-Zr alloys, amorphous, corrosion test, electrochemical measurement, NaCl and NaOH solutions. DOI: 10.3126/jncs.v25i0.3283 Journal of Nepal Chemical Society Volume 25, 2010 pp 37-45